Exploring the Relationship between Parental Oral Health Literacy and Children's Oral Health Status: A Cross-sectional study in an Iranian Population - Zahra Khoshkharam; Elham Charoghchian Khorasani (Mashhad University of Medical Sciences, 2024)
Background: Parents play a significant role in determining children's oral health behaviors. Oral health literacy (OHL) refers to on one's ability in understanding and employing oral health information in order to maintain good oral health. The aim of this study was to explore the relationship between parental OHL and children's oral health status.Methods and Materials: This descriptive-analytical cross-sectional study included female students attending a private school in Mashhad, Iran. This school was selected according to availability sampling. Students and their parents were invited to participate in this study and were enrolled using a census-based sampling method. Parents were asked to complete the oral health literacy standard questionnaire and their daughter's DMFT or dmft index was measured by an oral hygienist. Parents' demographic and social information were also recorded. The data was analyzed using SPSS version 26.00 statistical software. P-value<0.05 was considered statistically significant.Results: A total of 632 children participated in this study. Parents showed an average OHL score of 18.85±2.88. The average DMFT index of students was 2.04±2.27. There was a negative and statistically significant relationship between parent level of OHL and children's DMFT index as well as the number of decayed permanent teeth (P=0.020 and P=0.026, respectively). There was a positive and statistically significant correlation between parental OHL and the number of primary teeth with fillings (P=0.019). Family income was the only social factor that was significantly associated with the child's DMFT index (P<0.05). There was a significant correlation between parents' age, gender, educational degree, and occupation and their level of OHL (P<0.05 for all).Conclusion: The results of this study showed that promoting parental oral health can influence students' DMFT index. Therefore, developing interventions that can ameliorate parents' level of oral health literacy can improve the oral health outcomes of students.